Artificial intelligence-based spatio-temporal vision sensors: applications and prospects - Li, Zhixue; Sun, Hongwei (Frontiers in Materials, 2023)
Advances in machine vision and mobile electronics will be accelerated by the creation of sophisticated optoelectronic vision sensors that allow for sophisticated picture recognition of visual information and data pre-processing. Several new types of vision sensors have been devised in the last decade to solve these drawbacks, one of which is neuromorphic vision sensors, which have exciting qualities such as high temporal resolution, broad dynamic range, and low energy consumption. Neuromorphic sensors are inspired by the working principles of biological sensory neurons and would be useful in telemedicine, health surveillance, security monitoring, automatic driving, intelligent robots, and other applications of the Internet of Things (IoT). This paper provides a comprehensive review of various state-of-the-art AI vision sensors and frameworks. The fundamental signal processing techniques deployed and the associated challenges were discussed. Finally, the role of vision sensors in computer vision is also discussed.